Multifunctional polyelectrolyte microcapsules as a contrast agent for photoacoustic imaging in blood; Journal of Biophotonics; Vol. 9, iss. 8 - Yashchenok A. M. Alexey M.; Jithin J. Jose; Trochet Ph. Philippe; Sukhorukov G. B. Gleb Borisovich; Gorin D. A. Dmitry Aleksandrovich (2016, 2016)
Title screen